Heavenly ambitions : America's quest to dominate space - Johnson-Freese, Joan (EBL-Schweitzer, 2009)
In Heavenly Ambitions, Joan Johnson-Freese lays out her vision of the future of space as a frontier where nations cooperate, and military activity is circumscribed by arms control treaties that would allow no one nation to dominate--just as no one nation's military dominates the world's oceans.